2016
DOI: 10.1186/s13048-016-0278-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MDR genes expression and cross-resistance in eight drug resistant ovarian cancer cell lines

Abstract: BackgroundMultiple drug resistance (MDR) of cancer cells is the main reason of intrinsic or acquired insensitivity to chemotherapy in many cancers. In this study we used ovarian cancer model of acquired drug resistance to study development of MDR.We have developed eight drug resistant cell lines from A2780 ovarian cancer cell line: two cell lines resistant to each drug commonly used in ovarian cancer chemotherapy: cisplatin (CIS), paclitaxel (PAC), doxorubicin (DOX) and topotecan (TOP). A chemosensitivity assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 34 publications
6
89
0
Order By: Relevance
“…Expression of this gene was reported among others in breast and ovarian cancer and cancer cell lines (13)(14)(15)(16)(17). In our previous study we observed that TOP resistance could be also related to expression of glycoprotein P (P-gp) encoded by ABCB1 (MDR1) gene (16,18). Recently we reported the up-regulation of many collagen genes in TOPresistant ovarian cancer cell lines (19,20).…”
Section: Abstract Background: Low Effectiveness Of Chemotherapy In Omentioning
confidence: 94%
See 2 more Smart Citations
“…Expression of this gene was reported among others in breast and ovarian cancer and cancer cell lines (13)(14)(15)(16)(17). In our previous study we observed that TOP resistance could be also related to expression of glycoprotein P (P-gp) encoded by ABCB1 (MDR1) gene (16,18). Recently we reported the up-regulation of many collagen genes in TOPresistant ovarian cancer cell lines (19,20).…”
Section: Abstract Background: Low Effectiveness Of Chemotherapy In Omentioning
confidence: 94%
“…The main protein responsible for active removal of TOP from cancer cells is BCRP (breast cancer resistant protein) encoded by ABCG2 gene. Expression of this gene was reported among others in breast and ovarian cancer and cancer cell lines (13)(14)(15)(16)(17). In our previous study we observed that TOP resistance could be also related to expression of glycoprotein P (P-gp) encoded by ABCB1 (MDR1) gene (16,18).…”
Section: Abstract Background: Low Effectiveness Of Chemotherapy In Omentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] There has been much research on the mechanism of MDR in the recent years, 21,22 and scientists are trying to explore the mechanisms to overcome MDR such that chemotherapy drugs could exhibit a higher efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…P-gp discharges multiple cytoxic drugs using ATP within the cells, which increases the resistance of tumor cells to pharmacological agents, thereby causing the resistance of tumor cells (24). MDR1/P-gp is expressed in almost all human tumor cells to different degrees, and its expression in tumors insensitive to chemotherapy or with poor efficacy is often high (25). Previous studies have reported that the sensitivity of some cancer patients to chemotherapy was increased following the administration of P-gp inhibitors (24,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%